2019
DOI: 10.1038/s41598-019-42059-3
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, Double-blind, Placebo-controlled Study of a Multispecies Probiotic Mixture in Nonalcoholic Fatty Liver Disease

Abstract: The intestinal microbiota is closely associated with the development of obesity and nonalcoholic fatty liver disease (NAFLD). This study investigated the effects of probiotic treatment on visceral fat area (VFA) and intrahepatic fat (IHF) fraction in NAFLD. Sixty-eight obese NAFLD patients (>5% proton density fat fraction [PDFF] on magnetic resonance imaging [MRI]) were randomized to probiotic and placebo groups for 12 weeks. The probiotic mixture included 6 bacterial species. VFA and IHF were measured using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
95
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(110 citation statements)
references
References 29 publications
5
95
0
3
Order By: Relevance
“…In another study, reduction of triglycerides was more significant in the probiotic treatment group than in the placebo group. However, the changes in the percentage of intrahepatic fat fraction and triglyceride levels were not different between placebo and control groups after adjusting for changes in body weight [56].…”
Section: Probiotics/prebioticsmentioning
confidence: 76%
“…In another study, reduction of triglycerides was more significant in the probiotic treatment group than in the placebo group. However, the changes in the percentage of intrahepatic fat fraction and triglyceride levels were not different between placebo and control groups after adjusting for changes in body weight [56].…”
Section: Probiotics/prebioticsmentioning
confidence: 76%
“…Evidence from a randomized, double-blind, placebocontrolled study demonstrated that administration of a multispecies probiotic mixture reduces the intrahepatic fat and body weight in obese NAFLD patients (Ahn et al 2019). Animal studies have also shown that co-administration with cholesterol-lowering probiotics (two strains) and anthraquinone from Cassia obtusifolia L. has potential therapeutic effects for NAFLD (Mei et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Especially findings on Ruminococcus are rather controversial, as two other studies showed an increase in its presence in NAFLD suggesting that further studies are needed (34, 35). Only very few interventional studies in human NAFLD are so far available (27). This study assessed the effects of a probiotic treatment consisting of Lactobacillus acidophilus, L. rhamnosus, L. paracasei, Pediococcus pentosaceus, Bifidobacterium lactis , and B. breve on visceral and intrahepatic fat in NAFLD.…”
Section: Bacterial Dysbiosis In Nafldmentioning
confidence: 99%
“…TMA is produced by bacteria out of dietary compounds, in the liver it is further metabolized to TMAO, which leads to an increased risk for cardiovascular events (D) . Recently published data (27) show that a cocktail of prebiotics can reduce the intrahepatic fat content in steatotic patients (E) .…”
Section: Introductionmentioning
confidence: 99%